A multicenter evaluation on the impact of non-therapeutic transfer in rural trauma. Issue 1 (January 2023) - Bardes, James M.; Grabo, Daniel J.; LaRiccia, Aimee; Spalding, M. Chance; Warriner, Zachary D.; Bernard, Andrew C.; Dougherty, Melissa B. Linskey; Armen, Scott B.; Hudnall, Aaron; Stout, Conley; Wilson, Alison
Highlights: Non-therapeutic transfers are common in rural settings, encompassing up to one-third of trauma transfers in this analysis. Futile transfers were a small percentage of rural transfers, however they utilized a large amount of EMS and hospital resources, most commonly for severe traumatic brain injuries. Non-therapeutic transfers resulted in EMS traveling 76 min and 70 miles to transport a patient to a receiving hospital. Abstract: Introduction: Trauma transfers are a common occurrence in rural areas, where critical access and lower-level trauma centers routinely transfer to tertiary care centers for specialized care. Transfers are non-therapeutic (NTT) when no specialist intervention occurs, leading to transfer that were futile (FT) or secondary overtriage (SOT). This study aimed to evaluate the prevalence of NTT among four trauma centers providing care to rural Appalachia. Methods: This retrospective review was performed at four, ACS verified, Level 1 trauma centers. All adult trauma patients, transferred during 2018 were included for analysis. Transfers were considered futile if in <48 h the patient died or was discharged to hospice, without operative intervention. SOT transfers were discharged in <48 h, without major intervention, with an ISS< 15. Cost analysis was performed to describe the impact of NTT on EMS use. Results: 4, 189 patients were analyzed during the study period. 105 (2.5%) met criteria for futility. Futile patients had a median ISS of 25 (IQR 9–26), and 48% had an AIS head ≥4. These were significantly greater ( p <0.001) than non-futile transfers, median ISS 5 (IQR 2–9), 3% severe head injury. SOT occurred in 1371 (33%), median ISS of 5, and lower AIS scores by region. Isolated facial injuries resulted in 165 transfers. 13% of FT+SOT were admitted to the ICU. Only 22% of FT+SOT came from a trauma center. 68% were transported by ALS and 13% transported by air transport. FT+SOT traveled on average 70 miles from their home to receive care. Conclusions: Non-therapeutic transfers account for more than 1/3 of transfers in this rural environment. There was a significant use of advanced life support and aeromedical transport. The utility of these transfers should be questioned. With the recent increases in telehealth there is an opportunity for trauma systems to improve regional care and decrease transfers for futile cases.